MENINGKATKAN KETERAMPILAN SOSIAL MELALUI METODE BERMAIN PERAN PADA ANAK USIA DINI KELOMPOK A USIA 4-5 TAHUN DI PAUD SPS MELATI 1 GUNUNGBATU KECAMATAN CIRACAP - Sri Rahayu; Ibnu Hurri; Asep Munajat (CV. ADIBA AISHA AMIRA, 2024)
This research was motivated by the problems found in group A children at SPS PAUD Melati 1 Gunungbatu, Ciracap District regarding social skills. The alternative problem solving carried out in this research is to use the role playing method. The aim of this research is firstly, to find out how teachers implement the role playing method in improving the social skills of group A early childhood children at SPS PAUD Melati 1 Gunungbatu, Ciracap District, Academic Year 2022/2023. secondly, to find out the results of the teacher's application of the role-playing method to the social skills of group A early childhood children at SPS PAUD Melati 1 Gunungbatu, Ciracap District, Academic Year 2022/2023. This type of research uses Classroom Action Research (PTK) with descriptive-qualitative data analysis techniques. The research results show that there is an increase in children's social skills starting from the pre-cycle, action planning, namely cycle I to cycle II. The expected results were finally achieved in cycle II, namely that there were 80% of children with the Developing According to Expectations (BSH) criteria, 20% were starting to develop and there were no longer any students with the Not Yet Developing (BB) criteria.